Knowledge, attitudes, and practices of Kenyan healthcare workers regarding pediatric discharge from hospital - Paul, Shadae (My University, 2019)
The objective of this study was to assess attitudes, perceptions, and practices of healthcare workers regarding hospital discharge and follow-up care for children under age five in Nyanza Province, Kenya. From November 2017 to December 2018, we conducted a cross-sectional mixed methods study, involving online surveys of healthcare workers who deliver inpatient care to children at eight hospitals, followed by semi-structured telephone interviews to explore key areas in greater depth. Eighty percent (111) of eligible healthcare workers completed the survey. 104 (94%) felt that discharge care is “very important” to patient outcomes, but only 33% and 21% perceived that their hospital delivers discharge care and provides resources to deliver adequate discharge care “very well”, respectively. Of the international guidelines assessed in this study, the WHO Pocketbook of Hospital Care for Children was reportedly used the least (76%; 84). Participants reported various barriers to adequate use of the international and national guidelines, such as lack of availability and standardization of the guidelines. Respondents acknowledged the importance of follow-up care, however they reported that supportive mechanisms were either lacking or entirely non-existent at most participants’ hospitals. Ninety-seven percent of survey participants underestimated the risk of post-discharge morality. The post-discharge period is increasingly being understood by researchers as a very high-risk time for children. If improved discharge and follow-up care is to be achieved, our findings suggest that continuing education (i.e., pre-service and in-service training) should be enhanced to include best practices for discharge and follow-up care. Routine mortality reports in hospitals could be expanded to review adverse outcomes during hospitalization and in the post-discharge period. In addition, national and international guidelines for care require updating to expand sections on discharge and follow-up care. Finally, intervention trials are needed to assess the efficacy, effectiveness, and cost-effectiveness of packages to improve discharge and follow-up care.
Thesis (Master's)--University of Washington, 2019
Keywords: health policy; hospital re-admission; international guidelines; pediatric discharge care; pediatric follow-up care; post-discharge mortality; Public policy; Global Health